Optimization of selected heavy metals removal from anchovies using trisodium citrate and peracetic acid as chelating agent - Jaganazan, Pavitran; B Abdullah, Faizuan (Universitas Nahdlatul Ulama Surabaya, 2023)
Anchovy is widely used in many dishes and are among the most consumed marine fish among Malaysians. Anchovies are one of the marine organisms that can accumulate pollutants including heavy metals. Numerous studies were conducted to minimize the heavy metals concentration in seafood such as various cooking and processing methods, and advanced treatments with the aid of chelating agents. Among the effective methods to remove heavy metals from seafood is by chelating techniques. Previous research conducted showed that the removal of heavy metals from seafood with nanomaterials such as chelating agents enhances the quality of the seafood with reduced heavy metals concentration as well as minimum purification costs. In this research, combination of trisodium citrate and peracetic acid were used as the chelating agent to perform a series of optimization treatments to remove toxic heavy metals including arsenic (As), lead (Pb), cadmium (Cd), and chromium (Cr). The optimization treatment was conducted by using Box-Wilson central composite design (CCD) which is a model in response surface methodology (RSM). Among the parameters that were optimized in this study are temperature between 29.0 to 37.0℃, pH between 3 to 7, treatment time between 5 to 60 minutes, and dosage of chelating agent between 1000 to 2000 mL/Kg. The anchovy samples were prepared according to a method adopted from AOAC 999.10 standard method for elements cadmium, lead, arsenic, and chromium. Inductively coupled plasma optical emission spectrophotometer (ICP- OES) was used to determine the heavy metals concentration in untreated and treated anchovy samples. Analysis of variance (ANOVA) showed all the four models designed are significant and influence the percentage removal of heavy metals. The Design-Expert software based on CCD RSM suggested a total of 97 solutions according to the four independent variables. Based on the solutions suggested, an optimized condition selected with highest desirability at 0.644 with percentage removal of arsenic at 77%, lead 39%, cadmium 54%, and chromium 18%.